NUMERICAL COMPUTATIONS OF EXHAUST GASES JET FROM AIRCRAFT ENGINE UNDER IDLE OPERATIONAL CONDITIONS - Synylo, Kateryna; Krupko, Andrii; Zaporozhets, Oleksandr (Proceedings of National Aviation University, 2019)
Purpose: Currently models for airport air quality are based on the semi-empirical approaches for description of fluid dynamic of exhaust gases jet from aircraft engine and do not take into account an influence of the ground on jet behaviour and the interaction between the jet and the wing trailing vortex system. Eliminating the fluid mechanisms of aircraft wake vortex in models of airport air quality may overestimate the height of buoyancy exhaust gases jet from aircraft engine, underestimate its length and radius of expansion, dispersion characteristics and contaminants concentration values. Evaluation the entrainment and mixing processes of the engine emissions in the plume by using CFD-code is an actual task for airport air quality studies. Methods: Numerical investigation of properties and structure of aircraft engine jets with CFD codes (OpenFOAM) will give a realistic checked material, on the base of which a necessary scientific reasoning of transportation of the contaminants by engine jets. Results: Comparison between OpenFOAM numerical results and semi-empirical jet model calculations (used by complex model PolEmiCa) show that buoyancy effect parameters of exhaust gases decrease twice for wall jet. And the difference between appropriate longitudinal coordinate of buoyancy effect is near to 30%. Discussion: using CFD tool allows to improve an airport air quality analysis by providing more objective and accurate input data for further dispersion modelling.